1983
DOI: 10.1073/pnas.80.14.4208
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a specific phorbol ester aporeceptor in mouse brain cytosol.

Abstract: In the presence of phosphatidylserine, [20-3H]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(89 citation statements)
references
References 20 publications
5
84
0
Order By: Relevance
“…Identical requirements have been well documented for protein kinase C (26,27). In addition, similar requirements have recently been demonstrated for a soluble phorbol diester receptor found in several tissue types (31,32,49,50). In this study, optimal receptor binding and maximum kinase activity occurred at the identical Ca2" concentration of 10-' M. In addition, the relative mobilities of both activities from HL-60 cells on sizing chromatography are in accord with that found previously for protein kinase C from other sources (26,27).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Identical requirements have been well documented for protein kinase C (26,27). In addition, similar requirements have recently been demonstrated for a soluble phorbol diester receptor found in several tissue types (31,32,49,50). In this study, optimal receptor binding and maximum kinase activity occurred at the identical Ca2" concentration of 10-' M. In addition, the relative mobilities of both activities from HL-60 cells on sizing chromatography are in accord with that found previously for protein kinase C from other sources (26,27).…”
Section: Introductionsupporting
confidence: 90%
“…We found that stereospecific, saturable phorbol diester receptors copurified with protein kinase C activity through several steps. In addition, we confirmed the observation of PMA activation of protein kinase C. After initial submission of this paper, others have now demonstrated specific phorbol diester receptors in mouse brain cytosol that copurified with a Ca2+/ phospholipid-dependent kinase activity through gel filtration (31). Indeed, Ashendel et al (32,33), using detergent extracts of the particulate fraction of mouse brain, have shown copurification to apparent homogeneity of a specific phorbol diester receptor and a Ca2+/phospholipid-dependent protein kinase.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…The protein kinase C-phospholipid complex appears to be the phorbol ester binding site itself [26,27]. The divalent ionophore in the presence of external Ca2+ induces an increase in intracellular Ca2+ concentrations.…”
Section: % 02mentioning
confidence: 99%
“…Cytosohc 13H]PDBu binding was performed in a method similar to that described by Leach et al [15]. After stimulation for 15 min in culture flasks, the medium was aspirated and cells were scraped into 0.5 ml of ice-cold 'Kuo' buffer (20 mM Tris-HC1 (pH 7.5) 50 mM 2-mercaptoethanol, 2 mM EDTA and 1 mM phenylmethylsulphonyl fluoride) containing 0.01% leupeptin + 20 PM transepoxysuccinyl-rleucylamido-(4-guanidino)butane (E-64) and homogenised.…”
Section: Phorbof Binding Assaymentioning
confidence: 99%